2023
DOI: 10.3390/antiox12122094
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Mitigates RANKL and M-CSF Induced Osteoclast Differentiation via ROS-Dependent Mechanisms

Yang Yang,
Zhiyuan Liu,
Jinzhi Wu
et al.

Abstract: Nuclear factor-erythroid 2-related factor 2 (Nrf2) has been shown to be a negative regulator of osteoclast differentiation, but the precise mechanisms have not yet been established. We examined the precise roles of Nrf2 in regulating antioxidants and reactive oxygen species (ROS) levels, especially the cytoplasmic and mitochondrial ROS during osteoclastogenesis in vitro. In the current study, we found that the absence of Nrf2 promotes osteoclast differentiation in bone-marrow-derived macrophages (BMMs) and RAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Further investigation is required to clarify the role of NAC in macrophage polarization regulation. Additionally, —NAC has been observed to scavenge ROS in bone marrow-derived macrophages, RAW264.7 cells, and CD14+ peripheral blood monocytes under conditions promoting osteoclast differentiation induced by RANKL, M-CSF ( Aitken et al, 2004 ; Lee et al, 2005 ; Sakai et al, 2012 ; Cao and Picklo, 2014 ; Kim et al, 2018 ; Soares et al, 2019 ; Guo et al, 2020 ), H 2 O 2 ( Liu et al, 2021 ), Trimethylamine-N-oxide (TMAO) ( Wang et al, 2022 ), LPS ( Yan et al, 2020 ), ferric ammonium citrate (FAC) ( Jia et al, 2012 ), TRP14 knockout ( Hong et al, 2014 ), and NRF2 knockout ( Hyeon et al, 2013 ; Yang et al, 2023 ). By these manners, NAC can mitigate ROS and inhibit osteoclast differentiation via regulating redox signaling pathways, thereby reducing oxidative stress-mediated bone resorption ( Table 3 ).…”
Section: The Role Of Nac In Bone Microenvironmentmentioning
confidence: 99%
“…Further investigation is required to clarify the role of NAC in macrophage polarization regulation. Additionally, —NAC has been observed to scavenge ROS in bone marrow-derived macrophages, RAW264.7 cells, and CD14+ peripheral blood monocytes under conditions promoting osteoclast differentiation induced by RANKL, M-CSF ( Aitken et al, 2004 ; Lee et al, 2005 ; Sakai et al, 2012 ; Cao and Picklo, 2014 ; Kim et al, 2018 ; Soares et al, 2019 ; Guo et al, 2020 ), H 2 O 2 ( Liu et al, 2021 ), Trimethylamine-N-oxide (TMAO) ( Wang et al, 2022 ), LPS ( Yan et al, 2020 ), ferric ammonium citrate (FAC) ( Jia et al, 2012 ), TRP14 knockout ( Hong et al, 2014 ), and NRF2 knockout ( Hyeon et al, 2013 ; Yang et al, 2023 ). By these manners, NAC can mitigate ROS and inhibit osteoclast differentiation via regulating redox signaling pathways, thereby reducing oxidative stress-mediated bone resorption ( Table 3 ).…”
Section: The Role Of Nac In Bone Microenvironmentmentioning
confidence: 99%
“…Osteoporosis (OP) is a systemic bone disease characterized by damage to the bone microstructure and decreased bone mass, resulting in bone fragility and easy fracture [ 1 , 2 ]. Primary osteoporosis, as a major part of OP, is currently a major public health problem facing patients and medical practitioners globally.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that ENPP2 impacted cardiomyocyte ferroptosis by regulating the expression of GPX4, ACSL4, Nrf2, and AKT . Several studies showed that Nrf2 was translocated from the cytoplasm to nucleus during ferroptosis, inducing the expression of HO-1 and NQO1, both of which eliminated ROS . P53 was the regulation of cell cycle and apoptosis factors, through combining with GPX4 promoter to inhibit the GPX4 activity, causing ferroptosis .…”
Section: Introductionmentioning
confidence: 99%